2022
DOI: 10.1108/jfra-10-2021-0362
|View full text |Cite
|
Sign up to set email alerts
|

Intangible investment and non-financial performance of Egyptian firms: the moderating role of the COVID-19 pandemic

Abstract: Purpose This study aims to examine the impact of intangible investment on non-financial performance. This study also examines the moderating effect of the COVID-19 pandemic on this relationship. Design/methodology/approach This study extracted data from annual reports for a sample of Egyptian firms from 2012 to 2020. This study used the generalized method of moment for testing research. Findings This study finds that intangible investment positively affects non-financial performance and the COVID-19 pandem… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
9
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 7 publications
(9 citation statements)
references
References 46 publications
0
9
0
Order By: Relevance
“…The exclusion of these companies was based on the possibility that their negative net profit during the period from 2021 and 2022 is mainly influenced by Covid-19 consequences on the field. Tourism and Leisure sector in Egypt was one of the highly negatively affected sectors during Covid-19 (Sayed et al, 2022). The short period covered in this study might lead to bias in the results shown from this sector.…”
Section: Sample Selectionmentioning
confidence: 91%
“…The exclusion of these companies was based on the possibility that their negative net profit during the period from 2021 and 2022 is mainly influenced by Covid-19 consequences on the field. Tourism and Leisure sector in Egypt was one of the highly negatively affected sectors during Covid-19 (Sayed et al, 2022). The short period covered in this study might lead to bias in the results shown from this sector.…”
Section: Sample Selectionmentioning
confidence: 91%
“…This was measured on a 7-point Likert scale (1 = strongly disagree to 7 = strongly agree) by adopting the scale used by Kement et al (2022). Previous studies measured COVID-19 as a dummy variable equal to 1 in 2020 and 0 otherwise (Sayed et al , 2022). However, their study used longitudinal time series data that allowed COVID-19 to be measured as a dichotomous variable compared to the present study, which was cross-sectional.…”
Section: Methodsmentioning
confidence: 99%
“…Figure 1 shows the theoretical framework, which consists of four constructs: PMS, MCS use, pandemic-induced uncertainty and operational performance. The variable “PMS” is based on conventional theories of organizational structure known as the strategy–structure–performance paradigm (Sayed et al , 2022). Pandemic-induced uncertainty reflects the influence of the external environment on MCS use, which enhances performance if MCS use aligns with the external variable (Otley, 2016).…”
Section: Literature Reviewmentioning
confidence: 99%
See 1 more Smart Citation
“…Because if an investment is still using usury, maysir, gharar will harm economic activity. In addition, some things must be known, such as the influence of investment knowledge, investment motivation, and capital market training on investment decisions with investment interest as a mediation (Sayed et al, 2022).…”
Section: Literature Reviewmentioning
confidence: 99%